Clearance of senescent cells during cardiac ischemia–reperfusion injury improves recovery. Issue 10 (29th September 2020) - Dookun, Emily; Walaszczyk, Anna; Redgrave, Rachael; Palmowski, Pawel; Tual‐Chalot, Simon; Suwana, Averina; Chapman, James; Jirkovsky, Eduard; Donastorg Sosa, Leticia; Gill, Eleanor; Yausep, Oliver E; Santin, Yohan; et al.
Abstract: A key component of cardiac ischemia–reperfusion injury (IRI) is the increased generation of reactive oxygen species, leading to enhanced inflammation and tissue dysfunction in patients following intervention for myocardial infarction. In this study, we hypothesized that oxidative stress, due to ischemia–reperfusion, induces senescence which contributes to the pathophysiology of cardiac IRI. We demonstrate that IRI induces cellular senescence in both cardiomyocytes and interstitial cell populations and treatment with the senolytic drug navitoclax after ischemia–reperfusion improves left ventricular function, increases myocardial vascularization, and decreases scar size. SWATH‐MS‐based proteomics revealed that biological processes associated with fibrosis and inflammation that were increased following ischemia–reperfusion were attenuated upon senescent cell clearance. Furthermore, navitoclax treatment reduced the expression of pro‐inflammatory, profibrotic, and anti‐angiogenic cytokines, including interferon gamma‐induced protein‐10, TGF‐β3, interleukin‐11, interleukin‐16, and fractalkine. Our study provides proof‐of‐concept evidence that cellular senescence contributes to impaired heart function and adverse remodeling following cardiac ischemia–reperfusion. We also establish that post‐IRI the SASP plays a considerable role in the inflammatory response. Subsequently, senolytic treatment, at a clinically feasible time‐point, attenuates multiple components of this response and improves clinically important parameters. Thus, cellular senescence represents a potential novel therapeutic avenue to improve patient outcomes following cardiac ischemia–reperfusion. Abstract : Myocardial infarction and subsequent ischemia–reperfusion injury initiate senescence in multiple cell populations in the peri‐infarct region of the myocardium. Production of the SASP drives myocardial inflammation which promotes myocardial remodeling and inhibits angiogenesis. Treatment with the senolytic navitoclax reduced myocardial senescence and the associated SASP, resulting in a reduced scar size and increased vascularization which ultimately improved cardiac function.